Experimental characterization of enhanced SNCR process with carbonaceous gas additives. (June 2017) - Yao, Ting; Duan, Yufeng; Yang, Zhizhong; Li, Yuan; Wang, Linwei; Zhu, Chun; Zhou, Qiang; Zhang, Jun; She, Min; Liu, Meng
Abstract: Carbonaceous gases such as CO and alkanes are commonly used as additives to enhance the selective non-catalytic reduction (SNCR) performance due to their high reducibility. This study compared the effect of CO and CH4 on NO reduction in a tubular reactor with simulated flue gas. The enhancement of C3 H8 on SNCR process was tested at extremely low temperature, i.e. 650 °C. Experimental results suggested that reactions between NH3 and SO2 were favored at low temperatures and the competition for NH3 between SO2 and NO was influenced by gas additives. A maximum downward shift of 25 °C and 100 °C in temperature window for 50% NO reduction efficiency was obtained with the addition of CO and CH4, respectively. Considerable CO emission was observed with addition of CH4 . The addition of CH4 contributed to the formation of a self-accelerating reaction route within NO/O2 /NH3 SNCR reaction system. NO2 produced from NO accelerates the oxidation of CH4 to CO, while the oxidation of CH4 returns to enhance the NO reduction globally. Optimal NO reduction of 44% was achieved with addition of C3 H8 at 650 °C. Substantial portion of C3 H8 was partially oxidized to CO and the remaining was converted into C2 H4 and C3 H6 during the SNCR process. Oxidative dehydrogenation of C3 H8 was involved. High reactivity of C3 H6 and C2 H4 favored the further oxidation and cracking to produce CO. These differences in oxidation behavior significantly influence the promotion capacities of CO, CH4 and C3 H8 for NO reduction. Highlights: C3 H8 is particularly efficient in enhancing SNCR process at 650 °C. Mutual enhancement between CH4 oxidation and NO reduction is proposed. Competition for NH3 between SO2 and NO is affected by gas additives and temperature.